Exploring Regional Integration with Indo-Pacific Economies: A Background Analysis for IPEF Strategies - Francis Mark A. Quimba; Mark Anthony A. Barral (Philippine Institute for Development Studies (PIDS), 2023)
From the launch of the Indo-Pacific Economic Framework (IPEF), apprehension surrounds its true intentions and objectives. While touted as a US-led strategy to counter China's dominance in the region, IPEF seems to be a very slow-paced initiative and how it will progress, and how to go about it, remains a question that baffles economies. This paper presents IPEF's cohesiveness with the member economies and assesses IPEF's alignment with domestic policies and FTA commitments as well as in terms of priorities and visions, of the country. Considering the integration among IPEF partners, results suggest that IPEF is in fact aligned with the issues and policies of economies.
Keywords: 330; clean economy; clean energy; connectivity; cooperation; environment; fair economy; globalization; governance; IPEF; regional stability; security; supply chain; trade